TEACHING STUDENTS TO THINK CREATIVELY IN PRIMARY EDUCATION - Rakhimkulova Makhbuba Bakhranovna (International Journal of Innovations in Engineering Research and Technology, 2021)
This article discusses how to develop students' creative skills through independent work in their native language classes